Research on Data Risks and Regulations of Generative Artificial Intelligence - Li, Xinxin (Journal of Theory and Practice of Management Science, 2025)
With the disruptive development of generative artificial intelligence technology, the industrial structure has been optimized and upgraded, but it has also brought many data security risks in various stages of the application of artificial intelligence technology. There have been academic discussions both domestically and internationally on the regulation of risks related to artificial intelligence, in order to address a series of challenges such as data security and privacy protection caused by generative artificial intelligence. In order to address the above-mentioned risks and challenges, at present, China's governance of generative artificial intelligence should adhere to the principle of parallel risk prevention and research and development, follow basic ethical and moral principles, formulate specialized legal documents, build a unified regulatory system, establish autonomous mechanisms and other means to enrich the preventive and regulatory measures for generative artificial intelligence, in order to better respond to risks and challenges, and promote the coordinated and healthy development of generative artificial intelligence.